Study of the inactivation of spoilage microorganisms in apple juice by pulsed light and ultrasound - Ferrario, Mariana Inés (2015)
The aim of this study was to evaluate the effect of ultrasound (US) (600W, 20kHz and 95.2μm wave amplitude; 10 or 30min at 20, 30 or 44±1°C) and pulsed light (PL) (Xenon l& 3 pulses/s; 0.1m distance; 2.4J/cm2-71.6J/cm2; initial temperature 2, 30, 44±1°C) on the inactivation of Alicyclobacillus acidoterrestris ATCC 49025 spores and Saccharomyces cerevisiae KE162 inoculated in commercial (pH: 3.5; 12.5°Brix) and natural squeezed (pH: 3.4; 11.8°Brix) apple juices. Inactivation depended on treatment time, temperature, microorganism and matrix. Combination of these technologies led up to 3.0 log cycles of spore reduction in commercial apple juice and 2.0 log cycles in natural juice; while for S.cerevisiae, 6.4 and 5.8 log cycles of reduction were achieved in commercial and natural apple juices, respectively. In natural apple juice, the combination of US+60s PL at the highest temperature build-up (56±1°C) was the most effective treatment for both strains. In commercial apple juice, US did not contribute to further inactivation of spores, but significantly reduced yeast population. Certain combinations of US+PL kept on good microbial stability under refrigerated conditions for 15 days.